Increased splanchnic arterial vascular resistance in oldest old patients - Possible relevance for postprandial hypotension - Sieber, Cornel; et al. (Zeitschrift für Gerontologie und Geriatrie, 2007)
Objectives The aim of this study was to evaluate possible age-related changes in mesenteric artery and portal venous blood flow dynamics in relation to systemic haemodynamics in order to delineate putative haemodynamic changes relevant for postprandial hypotension in the elderly. Studies were performed over a wide age-range and for the first time in over 85-year-old patients. Design Superior mesenteric artery (SMA) parameters (diameter, peak systolic velocity, enddiastolic velocity, pulsatility index, volume flow) and portal vein (PV) parameters (diameter, portal vein velocity, volume flow) were measured by duplex ultrasound (General Electrics, Vivid 3) in 98 fasting subjects aged from 21 to 96 years. Systemic vascular parameters such as blood pressure, heart rate and cardiac output (echocardiography) were also determined. Excluded were patients with severe heart failure, liver cirrhosis, sepsis and those with mesenteric artery stenosis. Results Pulsatility index (PI) was positively correlated with age (r=0.33, p=0.015). In patients over 85 years, PI was significantly increased (p=0.002) as compared to younger controls. Cardiac output was negatively correlated with age (r=-0.247, p=0.005). The other haemodynamic parameters did not show age-dependent alterations. Conclusion The increase of PI in the SMA in patients over 85 years represents an increase of vascular resistance in the splanchnic area, because PI is sensitive to resistance changes of small arterial vessels. The pulsatility index in the splanchnic area seems to rise steeply in oldest old patients, probably as an attempt to compensate diminutions in cardiac output seen in this age group. These findings indicate that the splanchnic vascular bed is already used in the fasting state to guarantee systemic haemodynamics. Vasodilatation of this vascular bed as physiologically seen postprandially may therefore easily induce postprandial hypotension in the oldest old.
Keywords: pulsatility index; vascular resistance; splanchnic vessels; elderly; haemodynamics